Effect of beetroot extract on glucose-6-phosphate dehydrogenase, red blood cells, and their aggregation in a patient with Hereditary Spherocytosis: A case report - Al-Garawi, Zahraa Salim; Mahnna, Saif Ali; Hamed, Bilal Mahmoud; Al-Garawi, Ameen Youssef (Journal of medical and pharmaceutical sciences, 2024)
Hereditary spherocytosis is a hereditary disease results in the decomposition of spherical blood cells, leads to hemolytic anemia. Beetroot extract may be of a great therapeutic importance in its effect on hereditary spherocytosis and increase blood cells by continues uptake for a course. This study aimed to evaluate the effects of consuming beetroot extract for a period of five weeks on  a volunteer suffered hereditary and compared the results with a healthy volunteer. The effect of the extract on the red blood cells and hereditary spherocytosis was also studied. This study was carried out during February - April 2023 in the Department of Chemistry at Mustansiriyha University. The number of participants was only one suffered erythrocyte pleocytosis. The beetroot solution was diagnosed using high-performance liquid chromatography HPLC technique. Two-hindered mL of extract was consumed daily for a course of study continued to five weeks. The complete blood analysis and the activity of the enzyme Glucose-6-Phpdphate Dehydrogenase were estimated along the study course. The morphology of the red blood cells was examined by an electron microscope before and after drinking beetroot syrup over a period of five weeks. The results showed a relationship between beetroot extract and red blood cells for patient and healthy samples. Positive effects on the levels of hemoglobin and RBC over the study course for the patient. The extract reduced the incidence of anemia due to its nutritional importance that helped strengthen immunity and compensate for lost blood. Beetroot extract has also affected levels of  G6PDH. It increased the level of the enzyme after 3 weeks, inside the hemoglobin and RBC for both patient and control.
Keywords: beetroot extract; erythrocyte agglutination disease; glucose-6-phosphate dehydrogenase enzyme